Word-of-Mouth Marketing and Customer Acquisition: Experiences of Women Entrepreneurs in Makassar's Beauty and Wellness Industry - Riu, Isma Azis (Abadi Institute, 2025)
This phenomenological study explores how women entrepreneurs in Makassar’s beauty and wellness sector strategically leverage Word-of-Mouth (WOM) marketing as a relational economic mechanism for customer acquisition and retention. Anchored in a humanistic-economic perspective, the research examines how trust, emotional labor, and social capital function as non-financial assets that substitute for capital-intensive marketing strategies in resource-constrained contexts. Using Interpretative Phenomenological Analysis (IPA) on semi-structured interviews with salon owners, beauticians, and spa entrepreneurs, three superordinate themes emerged: (1) Trust as the Primary Economic Currency, emphasizing integrity and competence as foundations of customer advocacy; (2) Emotional Labor as Strategic Investment, highlighting empathy and personalized care as deliberate economic resources; and (3) The Social Network as Market Infrastructure, illustrating how localized community ties and digital interactions form efficient, low-cost distribution channels for business growth. The findings reveal that WOM in this sector is not merely a promotional outcome but a relational economic system rooted in cultural trust, affective commitment, and collective reciprocity. The study contributes to the literature by advancing a humanistic-economic framework for relational marketing, demonstrating how feminine entrepreneurship transforms social and emotional capital into measurable economic value.